Suffering in post-exilic times - investigating Mal 3:13-24 and Psalm 1 - Snyman, S. D. (Old Testament Essays, 2007)
The hypothesis investigated in this paper is that there is an intertextual link between Mal 3:13-24 and Psalm 1. It seems that the book of Malachi with its reference to the Torat Moshe ( hv,mo tr'/T) does not only link the last book of the Corpus Propheticum (or the Corpus Propheticum as a whole) to the first part of the Hebrew Bible, but it is at the same time also a pointer to what follows in the Writings, thereby connecting the second part of the Hebrew Bible / Old Testament (the Prophets) to the third part of the same corpus (the Writings).
free